Validation of equatorial electrojet derived from Swarm observations using ground based magnetometers - Ayebare, Daphine; Andima, Geoﬀrey; Mungufeni, Patrick; Jurua, Edward (Advances in Space Research, 2023)
This paper presents the analysis of the Equatorial electrojet (EEJS) and Counter equatorial electrojet (CEJS) at quiet times (Kp63) deduced from the absolute scalar magnetometers (ASM) of the Swarm satellites. The EEJS and CEJS were compared with their corresponding values, EEJG and CEJG respectively, from ground magnetometers in the South American, West African, and Asian sectors during the years 2014–2018. The results show that EEJS highly correlated with EEJG, over South American, West African and Asian sectors with correlation coeﬃcients of 0.91, 0.77 and 0.92 respectively. CEJS with CEJG also showed a reasonably good correlation of 0.78, 0.98 and 0.83 over South American, West African and Asian sectors respectively. For the ﬁrst time, the Swarm observations of CEJ and EEJ are validated against CEJ and EEJ from ground magnetometers, over South America, West Africa and Asia. Both the occurrence rates of CEJS and CEJG show similar diurnal and seasonal trends, with the highest occurrence rates in the morning (7:00–9:00 LT) and evening (15:00–19:00 LT) times and the lowest occurrence rates around noon (11:00 to 12:00 LT) time. The seasonal occurrence rates of CEJS and CEJG were high in the solstice months and the lowest rates were during equinox months for all the sectors. The longitudinal variability of CEJS and CEJG show highest occurrence rates in the West African sector and the lowest occurrence rates in the Asian sector. This longitudinal variability of CEJS and CEJG occurrence rates were attributed to the eﬀect of the non-migrating tides, migrating tides and stationary planetary waves. The annual occurrence rates of CEJS and CEJG seemed anti-correlated with F10.7.
Keywords: Low latitude ionosphere; Equatorial electrojet; Counter electrojet